Forgotten dust: following plasterboard for non-destructive circular economies - Rumo, Delphine (Frontiers in Sustainability, 2023)
The exploitative and unsustainable life of the construction material plasterboard requires more sustainable economies. In this article I examine the disposal of plasterboard as an experimental case for discussing a type of non-destructive circularity. A non-destructive circular model is one way to open imaginaries for more sustainable activities of construction. My focus is on end-of-life plasterboard, including its demolition, removal from construction sites, recycling and landfilling. Three months of fieldwork in the south of Finland clarified the current state of the material. I followed plasterboard across two building sites, two recycling facilities and a landfill site, and visually exposed disposal practices and material states to show the entanglement of workers, materials and circular economy discourses. The results highlight that plasterboard reproduces a problematic circularity that merely focuses on waste management through limited recycling, doing little to decrease the need for raw gypsum extraction. I outline how plasterboard in disposal conceptually disappears from the current economic model, which fails to address a variety of opportunities for more sustainable construction. By exposing a material reality that is concerned with small amounts of plasterboard in disposal, I show gypsum crumbs and dust which are unable to play a role in the current circular economy. However, I argue that attending to end-of-life plasterboard opens possibilities to imagine more ethical engagements with the material, towards non-destructive circularities. The disposal of plasterboard makes the inadequacy of the material for current circulation visible and can contribute to a debate on more sustainable economies of construction.